Structure and properties of cellular thin-walled cable coatings - Garbacz, T. (Polimery, 2012)
The paper describes the manufacturing process of cable and conduit double-layered coatings by cellular co-extrusion method. This coatings were obtained using poly(vinyl chloride) (PVC) and 0—0.5 wt. % of Adcol-blow UP-0Xb+X1020 as a blowing agent. The density and porosity of the produced samples were investigated. On the basis of their results the usefulness of obtained coatings to insulate electrical cables was evaluated.